Clinical utility of SPECT neuroimaging in the diagnosis and treatment of traumatic brain injury: a systematic review. - Cyrus A Raji; Robert Tarzwell; Dan Pavel; Howard Schneider; Michael Uszler; John Thornton; Muriel van Lierop; Phil Cohen; Daniel G Amen; Theodore Henderson (PLoS ONE)
Purpose This systematic review evaluated the clinical utility of single photon emission computed tomography (SPECT) in traumatic brain injury (TBI). Methods After defining a PICO Statement (Population, Intervention, Comparison and Outcome Statement), PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) criteria were applied to identify 1600 articles. After screening, 374 articles were eligible for review. Inclusion for review was focus on SPECT in the setting of mild, moderate, or severe TBI with cerebral lobar specificity of SPECT findings. Other inclusion criteria were comparison modalities in the same subjects and articles in English. Foreign language articles, SPECT studies that did not include comparison modalities, and case reports were not included for review. Results We identified 19 longitudinal and 52 cross-sectional studies meeting inclusion criteria. Three longitudinal studies examined diagnostic predictive value. The first showed positive predictive value increases from initial SPECT scan shortly after trauma to one year follow up scans, from 59% to 95%. Subsequent work replicated these results in a larger cohort. Longitudinal and cross sectional studies demonstrated SPECT lesion localization not detected by CT or MRI. The most commonly abnormal regions revealed by SPECT in cross-sectional studies were frontal (94%) and temporal (77%) lobes. SPECT was found to outperform both CT and MRI in both acute and chronic imaging of TBI, particularly mild TBI. It was also found to have a near 100% negative predictive value. Conclusions This review demonstrates Level IIA evidence (at least one non-randomized controlled trial) for the value of SPECT in TBI. Given its advantages over CT and MRI in the detection of mild TBI in numerous studies of adequate quality, and given its excellent negative predictive value, it may be an important second test in settings where CT or MRI are negative after a closed head injury with post-injury neurological or psychiatric symptoms.